Financial and Accounting: Meaning, Nature and Role of Accounting: Evolution and Importance of Accounting (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Accounting can be understood as the language of financial decisions. It is an on-going process of performance measurement and reporting the results to decision makers. The discipline of accounting can be traced back to very early times of human civilization. With the advancement of industry, modern day accounting has become formalized and structured. A person who maintains accounts is known as the account. The information generated by accounting is used by various interested groups like, individuals, managers, investors, creditors, government, regulatory agencies, taxation authorities, employee, trade unions, consumers and general public. Depending upon purpose and method, accounting 21 can be broadly three types financial accounting, cost accounting and management accounting. Financial accounting is primarily concerned with the preparation of financial statements. It is used on certain well-defined concepts and conventions and helps in framing broad financial policies. However, it suffers from certain limitations.